Immobilization of protease onto graphene oxide and rice husk - Muhammad Miqdad Razak (2013)
Immobilized enzyme has attracted great interest among the researchers and industry because of it high ability compare to none immobilized. In this study, protease from Aspergillus Oryzea was immobilized onto graphene oxide and rice husk by using simple absorption method. The activity test for immobilized enzyme was conducted respect to the temperature ability and possibility of reused. Both type of support was the new introduced material showed the high potential in the immobilization of enzyme. Rice husk can be the support for immobilized protease with improved temperature stability that has high activity at 50 ° C compare to other temperature. But the percent of immobilization of rice husk is low by 8% only at temperature 30 ° C. The graphene oxide also gives positive activity as support at temperature 30 ° C by 256 U/mL compare to the rice husk that is 17 U/mL, then the activity begin to reduce when the temperature rise. The percent of protease immobilized on graphene oxide is 49% at temperature 30 ° C. Both type supports showed the potential of reuse ability with reduced in activity after immobilized. Graphene oxide and rice husk was the suitable material as the support of protease. Both supports will give improve result if it is treated or immobilized using other methods.